Silicon Microring Resonators: PWM‐Driven Thermally Tunable Silicon Microring Resonators: Design, Fabrication, and Characterization (Laser Photonics Rev. 13(9)/2019). Issue 9 (10th September 2019) - Pintus, Paolo; Hofbauer, Michael; Manganelli, Costanza L.; Fournier, Maryse; Gundavarapu, Sarat; Lemonnier, Olivier; Gambini, Fabrizio; Adelmini, Laetitia; Meinhart, Carl; Kopp, Christophe; Testa, Francesco; Zimmermann, Horst; et al.
Abstract : In article number1800275, Paolo Pintus and co‐workers illustrate a typical microring‐based cross‐grid switching architecture in silicon photonics. The five shining colors in the cover image (red, yellow, green, blue, and purple) represent five distinct different wavelengths propagating from right to left in the switching architecture and the gray microring resonators located at the waveguide crossings are used as path switches. When hot (warm yellow color), each microring steers the signal path from the horizontal to the vertical direction.